2017
DOI: 10.1177/1941874417729981
|View full text |Cite
|
Sign up to set email alerts
|

Choosing Wisely Together: Physical and Occupational Therapy Consultation for Acute Neurology Inpatients

Abstract: A multifaceted intervention led to improved utilization of acute inpatient rehabilitation consultation while increasing the frequency of rehabilitation treatment for patients with highest functional impairment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 16 publications
1
18
0
Order By: Relevance
“…Previous research has examined methods for reducing therapy consults among patients with little to no physical impairment (Probasco et al, 2018). The results of the current study may further inform these efforts by showing that patients with goals of six or higher on the JH-HLM scale may not require physical therapy services to reach these goals, as nurses helped patients achieve these types of goals at similar rates in our sample.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Previous research has examined methods for reducing therapy consults among patients with little to no physical impairment (Probasco et al, 2018). The results of the current study may further inform these efforts by showing that patients with goals of six or higher on the JH-HLM scale may not require physical therapy services to reach these goals, as nurses helped patients achieve these types of goals at similar rates in our sample.…”
Section: Discussionsupporting
confidence: 51%
“…Studies have shown the benefits of interprofessional (i.e., nursing, physical therapy) approaches to mobility promotion among hospitalized patients, including decreased lengths of stay and fewer discharges to postacute care settings (Hoyer et al, 2016; Matharsa et al, 2021; van Delft et al, 2020). By engaging disciplines other than physical therapy (i.e., nursing) in mobility promotion efforts, patients can be mobilized more frequently and limited physical therapy resources can be targeted toward those in greatest need of their services (Probasco et al, 2018). Although this type of approach has been shown to be beneficial in postoperative populations (van Delft et al, 2020), it is unclear if patients with different mobility levels are more likely to achieve their mobility goals when seeing a physical therapist or a nurse.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the domains Beliefs about Consequences, Memory, Attention and Decision Process, and Social/Professional Role & Identity also contained many barriers. Several studies have targeted these domains to improve patients' physical activity levels, such as providing education to counter the belief that physical activity will result in injuries [86,88], using shift huddles to address prioritizing physical activity [89], or mapping the therapy consultation process within a multidisciplinary team to create role clarity and avoid unnecessary treatments [90]. Likewise, the domains Goals and Behavioural Regulation contained many enablers.…”
Section: Discussionmentioning
confidence: 99%
“…5 The AM-PAC score has been used to predict discharge destination within 48 hours of admission 6 and as a guide to allocate inpatient therapy referrals on a medical and a neurosurgical service. 7,8 To date, however, no studies have used AM-PAC scores to evaluate overutilization of physical therapy consults on direct care hospital medicine services. In this study, we aimed to assess the potential overutilization of physical therapy consults on direct care hospital medicine services using validated AM-PAC score cutoffs.…”
mentioning
confidence: 99%
“…The Activity Measure‐Post Acute Care Inpatient Mobility Short Form (AM‐PAC IMSF) is a validated tool for measuring physical function 5 . The AM‐PAC score has been used to predict discharge destination within 48 hours of admission 6 and as a guide to allocate inpatient therapy referrals on a medical and a neurosurgical service 7 , 8 . To date, however, no studies have used AM‐PAC scores to evaluate overutilization of physical therapy consults on direct care hospital medicine services.…”
mentioning
confidence: 99%